Hubungan antara Durasi Penggunaan Gadget dengan Perkembangan Sosial Anak Usia Prasekolah (4-5 tahun) di TA Ridwanussholihin Kota Malang - Maya Oktaviyanti Rismala; Achmad Dafir Firdaus; Reny Tri Febriani (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2024)
Introduction: The preliminary study at Ridwanussholihin Kindergarten in Malang City shows that there are still many preschool children who use gadgets for >1 hour. The relatively long use of gadgets in preschool children can have positive and negative impacts. Objectives: The purpose of this study is to determine the relationship between the duration of gadget use and the social development of preschool children (4-5 years old) at Ridwanussholihin Kindergarten in Malang City. Methods: This research applies a quantitative approach with the Cross-Sectional method. The application of the total sampling technique resulted in a sample size of 50 people. Data analysis through univariate analysis and bivariate analysis. Results: The results of the analysis showed that most of the respondents as many as 29 respondents (58%) were in the normal social development category, and the remaining 21 respondents (42%) were in the suspect development category. Then the proportion of respondents related to the duration of gadget use is relatively balanced, 25 people (50%) use gadgets for ≤ 1 hour (normal), and 25 people (50%) with a duration of > 1 hour (long). In the Spearman correlation test, the sig value <0.05 is 0.001, so the decision is that there is a positive and significant relationship between the duration of gadget use and the social development of preschool children. Discussion: Intense exposure to gadgets has limited stimulus and optimization of social development. Therefore, synergy between the school and parents in establishing policies regarding the use and supervision of gadgets is needed, as an effort to prevent the use of gadgets from replacing direct social interactions that are essential for children's development.